Polska (nie)gościnność we współczesnym reportażu - przybliżenia = Polish (un)hospitality in contemporary reportage - approximations - Dąbrowska, Dorota (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The purpose of the article is to reflect on one aspect of hospitality - the issue of openness of society to representatives of other cultures. According to popular beliefs and in the opinion of researchers of Polish traditions, hospitality is one of the fundamental characteristics of Polish culture. At the same time, however, it is also attributed to distance from others, distrust, and sometimes even xenophobia. The subject of the article`s analysis is contemporary Polish reportages showing Poland as an unfriendly country. The purpose of the study is not to treat reportages as credible sources of knowledge about Polish culture but to reflect on persuasive elements present in the story of difficulties in intercultural communication.
Keywords: reportaż; ksenofobia; gościnność; międzykulturowość; reportage; hospitality; xenophobia; interculturalism